Pendekatan Penggunaan Media Sosial Guna Memperluas Promosi dan Meningkatkan Perkembangan Bisnis Pelajar SMK N 1 SELO - Talita Putri Lestari; Alfiana Nahdiana; Ririn Dwi Ariani; Ika Ramadani; Novita Ambarwati (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The utilization of digital technology in the Industry 4.0 era has become crucial for vocational high school (SMK) students to build economic independence. However, partners at SMKN 1 Selo still face obstacles in optimizing social media and digital platforms as effective promotional tools for student work and self-development. This community service activity aims to enhance students' understanding and skills in using social media (Instagram, TikTok) and other digital platforms as creative marketing instruments. The method employed is a descriptive qualitative approach through participatory training, which includes material presentation on digital branding strategies, visual content creation practices, and copywriting techniques. The results of the activity indicate a significant improvement in students' technical abilities, where they demonstrated the capacity to produce engaging promotional content and understand social media algorithms to reach a wider audience. This study aims to describe the process and impact of utilizing social media and digital platforms as promotional tools for SMKN 1 Selo students. The primary focus of this activity is to provide a deep understanding of personal branding strategies and creative product marketing in the digital age. Through this program, it is expected that SMKN 1 Selo students will possess higher digital competitiveness and the ability to leverage the digital ecosystem to support the promotion of vocational products and their professional profiles in the future.